Refleksi Metafisis Atas Makna Substantif Carok dalam Budaya Madura - Ainur Rahman Hidayat (Jurnal Filsafat "WISDOM", 2003)
Carok is one of confict problem solving which is useng by Maduran by using a sharp tool like a knife called clurit of something like that. This paper reflects of that carok as a Maduran tradition whict contain humanistic value. Metaphisical reflection of carok tradition as relationalistic and substantionalistic were arranged of relation between one and many, static and dynamic, transcendence and immanent, social and individual.Substantionalistic substance consist of unique and difference motivation and the technic of carok it self.